2021
DOI: 10.1242/jeb.242138
|View full text |Cite
|
Sign up to set email alerts
|

The role of load-dependent sensory input in the control of balance during gait in rats

Abstract: Locomotor activity requires fine balance control that strongly depends on the afferent input from the load receptors. Following hindlimb unloading (HU), the kinematic and EMG activity of the hindlimbs is known to change significantly. However, the effects of HU on the integrative control mechanisms of posture and locomotion are not clear. The goal of the present study was to evaluate the center of mass (CoM) dynamic stabilization and associated adaptive changes in the trunk and hindlimb muscle activity during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…Changes in the locomotor activity of ST and BFp after HU were even more complex. In the previous study [36], we suggested that HU changed the ST activity differently throughout the step cycle during treadmill locomotion. Although the knee joint angle in the late stance was in hyperextension after HU [24], which theoretically led to the ST lengthening, the increase in the ST burst activity after HU is not likely to be associated with an increased activity of its I-a afferents.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the locomotor activity of ST and BFp after HU were even more complex. In the previous study [36], we suggested that HU changed the ST activity differently throughout the step cycle during treadmill locomotion. Although the knee joint angle in the late stance was in hyperextension after HU [24], which theoretically led to the ST lengthening, the increase in the ST burst activity after HU is not likely to be associated with an increased activity of its I-a afferents.…”
Section: Discussionmentioning
confidence: 99%